“Turning Points” For Aging Genealogists: Claiming Identities And Histories In Time - Hackstaff, Karla B. (Qualitative Sociology Review, 2009)
Based on qualitative in-depth interviews, I examine the use of genealogy with regard to the current historical moment for identities rooted in kin, race, class, gender, nation—and age. Drawing on the concept of “turning points” coined by Anselm Strauss, I explore moments that motivate the doing of family genealogy. First, I suggest that Strauss’s turning points may occur simultaneously and converge like vectors across time. Second, I argue that late middle-age lends itself to “identity extensions”, which I define as a reevaluation of self that acknowledges one or more of the following: the significance of extended kin to one’s identity; reverence for ancestors; a social responsibility to the future. Finally, I analyze how the current era informs a particular generation’s genealogical endeavors. I conceive of U.S. baby boomers’ genealogical projects as an expression of longing for connections in family lives and for a place in social history across the generations.